Argumentação e debates lingüísticos no Brasil - Ruben, Maria Victória R. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This article deals with the analysis of different answers given by some linguists to a question about their personal view of the debates in which they were engaged. This is an extension of a former research in which I analize some linguistic debates which took place in Brazil some years ago. Herewith, a linguistic methodology on argumentation analysis was developed, combining rhetoric with pragmatic perspectives. The results point out comprehension possibilities of a fundamental mechanism of the scientific history.